Diagnosis of myelin oligodendrocyte glycoprotein antibody-associated disease: International MOGAD Panel proposed criteria - Banwell, Brenda; Bennett, Jeffrey L; Marignier, Romain; Kim, Ho Jin; Brilot, Fabienne; Flanagan, Eoin P; Ramanathan, Sudarshini; Waters, Patrick; Tenembaum, Silvia; Graves, Jennifer S; Chitnis, Tanuja; Brandt, Alexander U; et al. (Lancet neurology, 2023)
Serum antibodies directed against myelin oligodendrocyte glycoprotein (MOG) are found in patients with acquired CNS demyelinating syndromes that are distinct from multiple sclerosis and aquaporin-4-seropositive neuromyelitis optica spectrum disorder. Based on an extensive literature review and a structured consensus process, we propose diagnostic criteria for MOG antibody-associated disease (MOGAD) in which the presence of MOG-IgG is a core criterion. According to our proposed criteria, MOGAD is typically associated with acute disseminated encephalomyelitis, optic neuritis, or transverse myelitis, and is less commonly associated with cerebral cortical encephalitis, brainstem presentations, or cerebellar presentations. MOGAD can present as either a monophasic or relapsing disease course, and MOG-IgG cell-based assays are important for diagnostic accuracy. Diagnoses such as multiple sclerosis need to be excluded, but not all patients with multiple sclerosis should undergo screening for MOG-IgG. These proposed diagnostic criteria require validation but have the potential to improve identification of individuals with MOGAD, which is essential to define long-term clinical outcomes, refine inclusion criteria for clinical trials, and identify predictors of a relapsing versus a monophasic disease course.